Literature Review : Manfaat Jahe (Ginger) untuk Kesehatan terkait Masalah Nyeri dan Mual Muntah - Antok Nurwidi Antara; Novi Istanti (Universitas Gorontalo, 2022)
Ginger is a plant that is commonly found in Indonesia. This plant is often used as a traditional herbal ingredient, food spices and even as herbal medicine or for health or complementary therapy by humans. This literature review study aims to determine the benefits of ginger (Ginger) for human health.This literature review uses a strategy by searching for article sources in national or international scientific research journals, from 3 search engines, namely: Pubmed keywords: ginger and therapy, Spingerlink keywords: ginger and therapy and Google Cendekia. Keywords: ‘Jahe dan Terapi’, restricted in 2020. Research using literature review methods from sample of 12 journals (2 Indonesian and 10 foreign), obtained information about the benefits of ginger for health, include: reducing pain in patients suffering from chronic low back pain, improving nasal symptoms and quality of life for patients with Allergic rhinitis ( AR), helps treat Diabetes Mellitus and reduces blood sugar levels, reduces pain in the knee in osteoarthritis patients, reduces nausea and vomiting in postoperative patients. The benefits of ginger for human health include: reduce pain, improve nasal symptoms and quality of life, help treat Diabetes Mellitus, reduce knee pain, reduce nausea and vomiting, inflammation, reduce menstrual pain